Comparative Characteristics of Informal Sector Workers in Kuta Beach Versus Sanur Beach - DPE Nilakusmawati; M Susilawati (Udayana Journal of Social Sciences and Humanities, 2018)
This study aims to compare the socio-economic characteristics of informal sector workers who run their business in the location of Kuta Beach, Badung-Bali versus Sanur Beach, Denpasar-Bali. Data were obtained from primary sources using questionnaires and sampling was done by purposive sampling. Informal sector workers who are respondents include street vendors, hawkers, masseuseers, photo artisans, souvenir vendors, and other personal services such as canoe rental, umbrellas rental, and others. The variable characteristics of the respondents were 15 variables of socioeconomics. Descriptive analysis is used to obtain an overview of socioeconomic characteristics of informal sector workers in the two sites studied. The result showed the average age of informal sector workers in Kuta beach is 50 years and Sanur 44 years. Working hours per day are not much different between two sites. The average income of respondents in Kuta Beach is lower than the average income of workers in Sanur. Workers in Kuta beach have been running relatively longer businesses compared to workers in Sanur beach. The relatively similar characteristics of workers between the two sites are sexes dominated by female workers, with marital status, mostly migrants with a length of stay of more than 5 years, with the status of homes occupied mostly by rent. Most workers in both sites are workers with self-employment status with workers of unpaid families. The findings of the study indicate a difference in the educational level of workers for the two comparable sites. There are also differences in the nature of merchandise services.